2006
DOI: 10.1038/sj.ijo.0803251
|View full text |Cite
|
Sign up to set email alerts
|

Simmondsin for weight loss in rats

Abstract: Objective: To investigate the safety and efficacy for weight loss of simmondsin, a dietary supplement extracted from the seed of the jojoba plant (Simmondsia chinensis). Animals: Sprague-Dawley male rats were fed various levels of simmondsin for 8 weeks (lean rats) or 16 weeks (high fat-induced obese rats). Measurements: Food intake, body weight and composition, histopathology, hematology parameters. Results: Simmondsin produced a clear dose-response effect on food intake and body weight. No remarkable histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The treatment with jojoba meal made it possible to remove these lipid droplets which show the non-toxicity of the jojoba meal on the kidney. Our results were in agreement with Boozer and Herron [39] who did not find a difference between the tissue structures of the kidneys of the untreated and simmondsin treated rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The treatment with jojoba meal made it possible to remove these lipid droplets which show the non-toxicity of the jojoba meal on the kidney. Our results were in agreement with Boozer and Herron [39] who did not find a difference between the tissue structures of the kidneys of the untreated and simmondsin treated rats.…”
Section: Discussionsupporting
confidence: 93%
“…Marnix et al [38] have worked with the same concentration of jojoba used in our study and the results showed that this concentration caused a reduction in the food intake and weight loss in the rats in 2 weeks. Boozer et Herron [39] proved that simmondsin produced a clear dose-response effect on this dietary intake as well as weight loss and that simmondsin at 0.15 and 0.25% significantly reduced these parameters without any undesirable effects. On the other hand, if this concentration is higher than 0.5%, many complications can be placed on the composition of white blood cells.…”
Section: Discussionmentioning
confidence: 98%
“…Although this theory cannot be excluded, the formation of cyanide as a by-product of digestion has yet to be demonstrated in animal studies 6 and the adverse effects of simmondsin are largely believed to be related to its anorectic effects. 6 7 …”
Section: Discussionmentioning
confidence: 99%
“…Simmondsin (5000 mg/kg p.o. ), obtained from Simmondsia chinensis, had no effect on food intake in rats fed on HFD for 16 weeks, but decreased body weight by 25% (Boozer and Herron, 2006).…”
Section: In Vivo Antiobesity Effectmentioning
confidence: 99%